2011
DOI: 10.1088/1748-9326/6/3/034014
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle greenhouse gas emissions of Marcellus shale gas

Abstract: This study estimates the life cycle greenhouse gas (GHG) emissions from the production of Marcellus shale natural gas and compares its emissions with national average US natural gas emissions produced in the year 2008, prior to any significant Marcellus shale development. We estimate that the development and completion of a typical Marcellus shale well results in roughly 5500 t of carbon dioxide equivalent emissions or about 1.8 g CO 2 e/MJ of gas produced, assuming conservative estimates of the production lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
281
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(299 citation statements)
references
References 7 publications
13
281
0
2
Order By: Relevance
“…These concerns include changes in air quality (6), human health effects for workers and people living near well pads (5), induced seismicity (7), and controversy over the greenhouse gas balance (8,9). Perhaps the biggest health concern remains the potential for drinking water contamination from fracturing fluids, natural formation waters, and stray gases (4, 10-12).…”
mentioning
confidence: 99%
“…These concerns include changes in air quality (6), human health effects for workers and people living near well pads (5), induced seismicity (7), and controversy over the greenhouse gas balance (8,9). Perhaps the biggest health concern remains the potential for drinking water contamination from fracturing fluids, natural formation waters, and stray gases (4, 10-12).…”
mentioning
confidence: 99%
“…The advantages of natural gas are even more favorable if the potential climate impact is assessed on time scales much longer than a decade. Jiang et al (26) evaluated the greenhouse gas (GHG) emissions resulting from the use of gas extracted from the Marcellus shale considering the entire life cycle of the gas.…”
Section: Discussionmentioning
confidence: 99%
“…They argued further, in contrast to Howarth et al (24), that the climate impact of the greenhouse gases emitted in conjunction with exploitation of the Marcellus shale source to produce electricity are significantly lower than those associated with the production of power using coal. They concluded that relatively straightforward measures could be implemented to minimize the potential release of greenhouse gases associated with the extraction of gas from shale (26). A more recent study by Hultman, et al (27) adopting a transparent and consistent approach to comparing the GHG footprints of conventional natural gas, shale gas, and coal, concluded that in terms of electricity generation the GHG impacts of shale gas are 11% higher than those for conventional gas (higher than the value reported by Jiang et al), but only 56% of the impact expected for coal.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the associated methane emissions from upstream activities, unconventional gas development has shown similar greenhouse footprint as coal. Table 9: Life cycle Greenhouse gas emissions from conventional natural gas (kg CO2-e/kWh) (Agrawal et al, 2014;Burnham et al, 2012;Hardisty et al, 2012;Howarth, 2014;Jiang et al, 2011;PACE, 2009;Stephenson et al, 2011) Reference Region…”
Section: Environmental Impact Regulations and Community Acceptancementioning
confidence: 99%
“…Greenhouse Table 10: Life cycle Greenhouse gas emissions from unconventional natural gas (kg CO2-e/kWh) (Burnham et al, 2012;Hardisty et al, 2012;Heath et al, 2014;Howarth, 2014;Jiang et al, 2011;Laurenzi and Jersey, 2013;Stephenson et al, 2011) Reference Type In Australia, the environmental regulations vary from state to state ( Figure 5). In particular, there are moratoria on hydro fracturing in Victoria and New South Wales (The Australian, 2014).…”
Section: Environmental Impact Regulations and Community Acceptancementioning
confidence: 99%